Open‐label study of faldaprevir plus peginterferon and ribavirin in hepatitis C virus genotype 1‐infected patients who failed placebo plus peginterferon and ribavirin. Issue 3 (17th November 2015) - Foster, G. R.; Ferenci, P.; Asselah, T.; Mantry, P.; Dufour, J.‐F.; Bourlière, M.; Forton, D.; Maevskaya, M.; Wright, D.; Yoshida, E. M.; García‐Samaniego, J.; Oliveira, C.; et al.
Summary: Faldaprevir, a hepatitis C virus (HCV) NS3/4A protease inhibitor, was evaluated in HCV genotype 1‐infected patients who failed peginterferon and ribavirin (PegIFN/RBV) treatment during one of three prior faldaprevir trials. Patients who received placebo plus PegIFN/RBV and had virological failure during a prior trial were enrolled and treated in two cohorts: prior relapsers ( n = 43) and prior nonresponders (null responders, partial responders and patients with breakthrough; n = 75). Both cohorts received faldaprevir 240 mg once daily plus PegIFN/RBV for 24 weeks. Prior relapsers with early treatment success (ETS; HCV RNA <25 IU/mL detectable or undetectable at week 4 and <25 IU/mL undetectable at week 8) stopped treatment at week 24. Others received PegIFN/RBV through week 48. The primary efficacy endpoint was sustained virological response (HCV RNA <25 IU/mL undetectable) 12 weeks post treatment (SVR12). More prior nonresponders than prior relapsers had baseline HCV RNA ≥800 000 IU/mL (80% vs 58%) and a non‐CC IL28B genotype (91% vs 70%). Rates of SVR12 (95% CI) were 95.3% (89.1, 100.0) among prior relapsers and 54.7% (43.4, 65.9) among prior nonresponders; corresponding ETS rates were 97.7% and 65.3%. Adverse events led to faldaprevir discontinuations in 3% of patients. The most common Division of AIDS Grade ≥2 adverse events were anaemia (13%), nausea (10%) and hyperbilirubinaemia (9%). In conclusion, faldaprevir plus PegIFN/RBV achieved clinically meaningful SVR12 rates in patients who failed PegIFN/RBV in a prior trial, with response rates higher among prior relapsers than among prior nonresponders. The adverse event profile was consistent with the known safety profile of faldaprevir.